ON THE INFLUENCE OF PRELIMINARY TERRITORIAL DIVISION ON RESULTS OF ZOOGEOGRAPHIC REGIONALIZATION - Yu. Ravkin S.; I. Bogomolova N.; O. Nikolaeva N.; Ю. Равкин С.; И. Богомолова Н.; О. Николаева Н. (Izvestiya Rossiiskoi Akademii Nauk Seriya Geograficheskaya, 2017)
Increasing by 2.5 times the number of portions in preliminary division of the territory in accordance with the faunistic classification has resulted in lower correspondence between the defined latitudinal belts and zonal boundaries. This affected the area of Central (temperate) region due to its expansion farther north and inclusion of East Siberian mountain enclaves, parts of forest-tundra and true tundra landscapes with addition of the entire Chukotka Peninsula in northeast. Expansion of a similar scale takes place in the south of the region at the expense of the territories adjacent to Black and Caspian seas as well as Caucasus area and most of the forest-steppe zone. With finer division of the initial regional grid, the classification algorithm used in the study results in concepts, which are more generalized on a regional scale. The consequent division would detail the result of classification. Finally, we conclude that increased number of portions of relatively equal area better shows the continuality and provincial specifics of fauna, whereas the decreased number of portions of bigger area better reflects zonal differences. Предварительное деление территории при фаунистической классификации на большее в 2.5 раза количество участков привело к меньшему совпадению выделенных широтных полос с зональными границами. При этом площадь Срединного региона возросла за счет расширения к северу и стала включать горные анклавы Восточной Сибири и часть лесотундровых и тундровых ландшафтов, а на северо-востоке – почти всю Чукотку. Аналогичное расширение границ этого региона происходит в южном направлении за счет причерноморских, прикаспийских и кавказских территорий, а также бóльшей части лесостепи. В целом, при использованном алгоритме классификации, более дробное деление на участки приводит к более обобщенным, на региональном уровне, представлениям и большей детальности при дальнейшем разделении. В результате, при большем числе участков с более или менее сходной площадью лучше отражается континуальность и провинциальная специфика фауны, в то время как меньшее число участков и бóльшие размеры подчеркивают зональные отличия.